Shale reservoir characteristics of Ordovician Wufeng-Silurian Longmaxi formations in Dangyang synclinorium, Middle Yangtze region - Jiawei FAN; Kongquan CHEN; Junjun SHEN; Wei ZHU; Xiehua TANG; Junjun LI; Pengwan WANG; Fang ZHANG (Shiyou shiyan dizhi, 2020)
The petrological and organic geochemical characteristics, reservoir porosity types and features, and gas-bearing characteristics of organic-rich shale were systematically studied using FIB-SEM, mineral contentanalysis, organic geochemical analysis and low-temperature and low-pressure nitrogen adsorption porosity determination, and drilling data of typical wells in the Dangyang synclinorium. (1) Vertically, shale reservoirs from the Wufeng Formation(O3w) are quite different from the first section of the first member of Longmaxi Formation (S1l11). High-quality shale reservoirs are developed from S1l11(1) to S1l11(2) sublayers, with a high abundance of organic matter (2.45%-6.98%), type Ⅱ1-Ⅱ2 organic matter, rather high thermal evolution degree, high brittle mineral content (34.0%-85.5%), low clay mineral content (9.0%-40.3%), and high total gas content (1.76-4.30 m3/t). Organic pores are well developed. In the S1l11(3) sublayer, affected by the intensified Caledonian tectonic activity, terrigenous material input increased, and reservoir quality began to deteriorate. (2) Horizontally, organic-rich shale of the Wufeng-Longmaxi formations in the Dangyang synclinorium become thicker from southeast to northwest, and the reservoir quality becomes better. (3) Shale reservoirs in the S1l11(1)-S1l11(2) sublayers in the study area are the "sweetest" and the "most brittle".However, considering the convenience of real-time monitoring and adjustment of well trajectory during horizontal drilling, the upper and lower half of GR peak in the S1l11(1) sublayer should be selected as the best horizontal target of horizontal wells.